Analisis Komposisi Gizi dan Serat Pangan Kukis Substitusi Tepung Jantung Pisang untuk Diversifikasi Pangan Lokal: Nutritional Composition and Dietary Fiber Analysis of Banana Blossom Flour Substituted Cookies for Local Food Diversification - Wiwi Febriani; Ramadhana Komala; Dian Isti Angraini; Sofyan Musyabiq Wijaya; Andi Eka Yunianto (Amerta Nutrition, 2025)
Background: Local food varies, with a lesser reliance on wheat flour and the incorporation of local foods such as banana flower, which is high in fiber and nutrients. The incorporation of banana flower may allow for a healthy snack using wheat flour-based cookies while increasing the potential for developing local food sources. Objectives: The objective of this study was to determine the nutritional composition and dietary fiber of wheat flour cookies that have banana flower flour as a substitute. Methods: An experiment employing a Completely Randomized Design (CRD) was conductssed using four levels of wheat and banana flour substitution, F0 (100:0), F1 (85:15), F2 (70:30), and F3 (55:45). Each formula had two replicates. Analysis of Proximate composition was performed for moisture (via oven), ash (via gravimetric), protein (via Kjeldahl), fat (by difference), crude and dietary fiber (via enzymatic gravimetric methods). Data were analyzed using one-way ANOVA (α = 0.05). Results: A one-way ANOVA analysis showed the following significant differences (p-value<0.05) between the formulas. In terms of the moisture content (1.55-3.17%), ash (2.13-3.72%), protein (6.13-7.68%), fat content (26.59 to 28.29%), crude fiber (3.40 - 5.79%) and dietary fiber (10.10 - 16.75%), while carbohydrate content (60.28 to 60.96%) were found to be not significant when comparing the formulas to F3 which had the highest protein, ash, crude fiber and fiber dietary types, while in reverse, the fat and water levels of each formula decreased when increasing the amount lemon flower flour (using banana flour) was substituted. Conclusions: Incorporating banana flower flour into cookie recipes has improved protein, ash, and fiber levels. It could improve the healthfulness of cookies and support local food diversity.